Comunicação LoRa cooperativa com codificação de rede - Alves, Luis Henrique de Oliveira (2021)
With the widespread adoption of Internet-of-Things (IoT) devices, new approaches to help countervene the effects of collisions in networks based on the LoRa modulation, and more specifically on LoRaWAN, are needed. With this objective in mind, this work investigates the performance of a scheme based on the concept of network coded cooperation (NCC) called NCC-LoRa. In it, devices exchange messages with each other in a Device to Device (D2D) fashion through Frequency Shift Keying (FSK) modulation under a high bit rate. The devices can then provide mutual assistance and improve communication reliability with the common GateWay (GW) by performing linear combinations over a finite field of the messages from each cooperating partner. The probability of success in the D2D communication is modeled from two components: the probability of effective data transmission, which computes failures arising from data exchange, and the neighborhood probability, which depends on factors associated with the network topology. Then, the performance of the network with NCC-LoRa is verified on the metrics of network range and average consumption of electric current per transmission cycle. The attained results show that the proposed scheme can provide considerable gains in these terms when compared to a typical LoRa transmission and to a scheme based on packet retransmission.